Planning for diversity : options and recommendations for DoD leaders - Lim, Nelson (Rand, 2008)
Despite the U.S. armed forces' historical role as a model for racial integration and decades of Department of Defense (DoD) efforts to promote racial and ethnic diversity, many groups are still underrepresented within the department, especially among DoD's active duty and civilian leadership. This is a particularly important issue for DoD because many military leaders believe that maintaining a diverse workforce is critical for the department's national security mission. This report discusses the initial steps that DoD should take in developing a department-wide plan to achieve greater diversity within its active duty and civilian leadership. To create a strategic plan for diversity, the authors explain, DoD leaders must articulate a vision for where they want the organization to go, and this vision statement must clearly define what type of diversity DoD wants to achieve. The next step is to set specific goals for the various components of DoD and to develop strategies for meeting those goals. Finally, Lim, Cho, and Curry emphasize that the strategic plan will fail unless there are ways to both measure the progress toward the plan's goals and hold leaders accountable for such progress. The report draws on findings from the DoD Diversity Summit held in Washington, D.C., on February 27-28, 2007, and includes an appendix that summarizes presentations and discussions from the summit.